'The secret to success'. Becoming a successful student in a fast-changing higher education environment. Issue 4 (1st October 2020) - José Sá, Maria
ABSTRACT: The literature on higher education student success offers a considerable set of definitions of this concept, reflecting its semantic polysemy. This is understandable, inasmuch that the highly competitive environment where higher education institutions operate requires that they constantly seek legitimation and competitive advantage based on their students' success. The purpose of this paper is to understand how the different institutional actors perceive and define higher education student success. The study uses a qualitative methodology and data collection instruments used are semi-structured interviews and document analysis. Results allow concluding that, according to the institutional actors' perceptions, defining success based solely on academic performance is reductionist and limits this concept to only one sphere of the students' global experience. The result of academic performance is a quantitative indicator of student success; however, while being necessary, it is not sufficient to define this concept. This indicator has to be complemented by others so that it can be ascertained whether or not a student has achieved success. Students build their perceptions of success based on the multiplicity and complexity of experiences they go through in higher education, influenced by the HEI features and mediated by their personal history and their life project.